TALEN-mediated site-directed mutagenesis of HLH proteins lyl1 and Id4 to reveal their role in haematopoietic and neural stem cell fate - Dhanaseelan, Tamilvendhan (2016)
Basic Helix-Loop-Helix proteins are transcriptional regulators crucial for many development processes. Using gain- and loss-of-function analysis in zebrafish, the functional role of two members of this protein family, lyl1 (Lymphoblastic leukaemia 1) and Id4 (Inhibitor of differentiation 4) in stem cell fate was determined. Ectopic overexpression of lyl1 resulted in the expansion of haematopoietic stem cell pool and its progeny promoting erythrocyte differentiation and suppressing myeloid differentiation. TALEN-mediated lyl1-/¬- embryos developed normally but displayed distinct marker gene expression during primitive and definitive haematopoiesis establishing a role for lyl1 in both waves of haematopoiesis. During primitive haematopoiesis expression of scl/tal1 and gata1 was unaltered but expression of pu.1 was increased suggesting that lyl1 antagonises myeloid differentiation. Lyl1-deficiency resulted in reduction of Gfi1aa expression during primitive and definitive haematopoiesis. In addition, a reduction in the expression of c-myb in the caudal hematopoietic tissue and rag1 in the thymus was observed indicating that lyl1 is required to maintain the definitive haematopoietic stem cell pool and to drive T lymphopoiesis. In adult zebrafish lyl1 regulates lineage choice driving lymphopoiesis and suppressing myelopoiesis. Morpholino-mediated knockdown of Id4 alone or in combination with p53 resulted in reduced cell proliferation, increased cell death and premature neuronal differentiation. Phenotypic analysis of TALEN-mediated Id4 mutants confirmed that Id4 plays a crucial role in the expansion of neural stem cells and timing of neuronal differentiation. Inhibition of p38MAPK in Id4 morphants as well as Id4-/- mutants resulted in a phenotypic rescue establishing that Id4 negatively regulates p38MAPK activity to ensure normal neurogenesis.